The Importance of Stem Photosynthesis for Two Desert Shrubs Across Different Groundwater Depths - Liu, Ran; Feng, Xiaolong; Li, Congjuan; Ma, Jie; Wang, Yugang; Li, Yan (Frontiers in Plant Science, 2022)
Water availability could alter multiple eco-physiological processes such as water use strategy, photosynthesis, and respiration, thereby modifying plant water use and carbon gain. However, the lack of field observations hinders our understanding on how water availability affects stem photosynthesis at both organ- and plant- level of desert shrubs. Here, we measured gas exchange and oxygen stable isotopes to quantify water sources, stem recycling photosynthesis, and whole-plant carbon balance in two co-existing Haloxylon species (Haloxylon ammodendron and Haloxylon persicum) at different groundwater depth in the Gurbantonggut Desert. The overall aim of the study was to analyze and quantify the important role of stem recycling photosynthesis for desert shrubs (Haloxylon species) under different groundwater depth. The results showed that 1) regardless of changes in groundwater depth, H. ammodendron consistently used groundwater and H. persicum used deep soil water as their main water source, with greater than 75% of xylem water being derived from groundwater and deep soil water for the two species respectively; 2) stem recycling photosynthesis re-fixed 72%-81% of the stem dark respiration, and its contribution to whole-plant carbon assimilation was 10%-21% for the two species; 3) deepened groundwater increased stem water use efficiency and its contribution to whole-plant carbon assimilation in H. persicum, but not in H. ammodendronOur study provided observational evidence that deepened groundwater depth induced H. persicum to increase stem recycling photosynthetic capacity and a greater contribution to whole-plant carbon assimilation, but this did not occur on H. ammodendron. Our study indicates that stem recycling photosynthesis may play an important role for the surviving of desert shrubs in drought conditions.